Berry size and seed number of V. myrtillus and E. hermaphroditum according to treatment, and environmental parameters 1991-2009 at Abisko Research Station - Dylan Gwynn-Jones; Alan G Jones; Alice Waterhouse; Ana Winters; David Comont; John Scullion; Rosie Gardias; Bente J Graae; John A Lee; Terry V Callaghan (PANGAEA, 2012)
This study investigated the effects of long-term-enhanced UV-B, and combined UV-B with elevated CO2 on dwarf shrub berry characteristics in a sub-arctic heath community. Germination of Vaccinium myrtillus was enhanced in seeds produced at elevated UV-B, but seed numbers and berry size were unaffected. Elevated UV-B and CO2 stimulated the abundance of V. myrtillus berries, whilst UV-B alone stimulated the berry abundance of V. vitis-idaea and Empetrum hermaphroditum. Enhanced UV-B reduced concentrations of several polyphenolics in V. myrtillus berries, whilst elevated CO2 increased quercetin glycosides in V. myrtillus, and syringetin glycosides and anthocyanins in E. hermaphroditum berries. UV-B x CO2 interactions were found for total anthocyanins, delphinidin-3-hexoside and peonidin-3-pentosidein in V. myrtillus berries but not E. hermaphroditum. Results suggest positive impacts of UV-B on the germination of V. myrtillus and species-specific impacts of UV-B x elevated CO2 on berry abundance and quality. The findings have relevance and implications for human and animal consumers plus seed dispersal and seedling establishment.
Supplement to: Gwynn-Jones, D et al. (2012): Enhanced UV-B and Elevated CO2 Impacts Sub-Arctic Shrub Berry Abundance, Quality and Seed Germination. AMBIO, 41(3 SU), 256-268, https://doi.org/10.1007/s13280-012-0311-4